Liver Injury Patterns and Hepatic Toxicity among People Living with and without HIV and Attending Care in Urban Uganda - Clara Wekesa; Rosalind Parkes-Ratanshi; Gregory D. Kirk; Ponsiano Ocama (International Journal of Hepatology)
Introduction. The evaluation of the patterns of liver injury, derived from liver chemistry panels, often may narrow on probable causes of the liver insult especially when coupled with clinical history, examination, and other diagnostic tests. Methods. Among people living with and without HIV and attending care, we used the R ratio to evaluate for liver injury patterns. Liver injury patterns were defined as cholestatic (R<2), mixed (R=2‐5), and hepatocellular (R>5). Results. Overall, the proportions of participants with cholestatic liver injury, mixed liver injury, and hepatocellular liver injury were 55%, 34%, and 4%, respectively, with similar distribution when stratified by HIV status. Alcohol use among participants without HIV was associated with all patterns of liver injury (cholestatic liver injury (OR=4.9 CI (1.0-24.2); p=0.054), mixed liver injury (OR=5.3 CI (1.1-27.3); p=0.043), and hepatocellular liver injury (OR=13.2 CI (1.0-167.3); p=0.046)). Increasing age was associated with cholestatic liver injury among participants with HIV (OR=2.3 CI (1.0-5.3); p=0.038). Despite a high hepatitis B prevalence among participants with HIV, there was no association with liver injury. Conclusions. Liver injury is prevalent among both people living with and without HIV in care, and cholestatic liver injury is the most common pattern. Alcohol is associated with all patterns of liver injury and increasing age associated with cholestatic liver injury among people living without HIV and people living with HIV, respectively.